2017
DOI: 10.1016/j.celrep.2017.10.071
|View full text |Cite
|
Sign up to set email alerts
|

Sub-minute Phosphoregulation of Cell Cycle Systems during Plasmodium Gamete Formation

Abstract: SummaryThe transmission of malaria parasites to mosquitoes relies on the rapid induction of sexual reproduction upon their ingestion into a blood meal. Haploid female and male gametocytes become activated and emerge from their host cells, and the males enter the cell cycle to produce eight microgametes. The synchronized nature of gametogenesis allowed us to investigate phosphorylation signaling during its first minute in Plasmodium berghei via a high-resolution time course of the phosphoproteome. This revealed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 41 publications
8
63
0
Order By: Relevance
“…PbKIN8B could also interact with one or several axonemal proteins among several motor proteins (as dyneins and kinesins, among which are kinesin-13 and -15, expressed in male gametogenesis) (Szklarczyk et al, 2015) (Invergo et al, 2017). The project was approved by the Ethic Committee CUVIER (authorization n°68-007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PbKIN8B could also interact with one or several axonemal proteins among several motor proteins (as dyneins and kinesins, among which are kinesin-13 and -15, expressed in male gametogenesis) (Szklarczyk et al, 2015) (Invergo et al, 2017). The project was approved by the Ethic Committee CUVIER (authorization n°68-007).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a number of critical transcription factors and epigenetic regulators have emerged as crucial elements in the regulation of Plasmodium sexual commitment, allowing a better understanding of the events occurring prior to and during commitment to sexual development (Filarsky et al, 2018;Kafsack et al, 2014;Kent et al, 2018;Sinha et al, 2014). During the last years, several proteomic studies identified proteins present during the sexual stages and recently the importance of phosphoregulation was highlighted during gametogenesis (Garcia et al, 2018;Invergo et al, 2017;Khan et al, 2005;Talman et al, 2014). However, surprisingly little is known about the dramatic processes and the actors leading to free motile male gametes e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Female gametocytes also mature and exit their host cells upon entering a mosquito but no replication or cell division occurs.) In the model rodent malaria species P. berghei , in which much of the work on gametocytes has been conducted, the first round of replication is usually completed within a minute of gametocyte activation [ 32 ]. Such extreme speed is unprecedented in eukaryotic gametogenesis, and may reflect strong pressure to complete the sexual cycle and exit the midgut before the parasite cells are digested along with the blood meal.…”
Section: Mechanics Of Dna Replication At the Molecular Levelmentioning
confidence: 99%
“…Together, this data combined with available genomic, transcriptomic, and proteomic information would help to construct more reliable and complete regulatory and metabolic networks giving us a holistic insight into the lifestyle of this peculiar parasite. epigenetic (363,364) and phosphoregulatory (365,366) factors in this complex regulatory network driving parasite development has been demonstrated to date.…”
Section: Future Prospectsmentioning
confidence: 99%